Distribution Patterns of Juvenile Spotted Seatrout (Cynoscion nebulosus) and Red Drum (Sciaenops ocellatus) Along Shallow Beach Habitats in Pamlico River, North Carolina - Powers, J. Phillip (East Carolina University, 2012)
The association of juvenile spotted seatrout (Cynoscion nebulosus) and red drum (Sciaenops ocellatus) with Submerged Aquatic Vegetation (SAV) is well documented. However, their association with other estuarine habitats including shallow (non-vegetated) sandy areas is not well understood. The goal of this project was to evaluate habitat use and distribution of juvenile spotted seatrout and red drum along shallow habitats in Pamlico River, North Carolina. The specific objectives were: 1) to evaluate the spatiotemporal patterns of juvenile spotted seatrout and red drum distribution; 2) to determine the effect of habitat type (SAV, sand, and detritus) on growth and mortality; 3) to determine the accuracy and precision in estimating fish age from otoliths with two methods: polishing and oil immersion; and 4) to distinguish how fish community structure (intraspecific and interspecific networks) may affect the presence of juvenile spotted seatrout and red drum distribution in the fish community. Pamlico River was divided into three 21.6-km strata from Fork Point Island westward, to the mouth of the Pungo River. The three areas were identified as West, Central, and East and each contained six fixed stations. Juvenile spotted seatrout and red drum were collected twice a month with an 18-m beach seine from August through November 2009 and 2010. Three substrate samples at each site were also collected once during the second sampling season. All fish were weighed (nearest 0.01 mg), measured (TL, SL in mm). Size (TL) ranged from 30 to 160 mm TL for spotted seatrout and from 15 to 65 mm TL for red drum. The West area of Pamlico River had the highest abundance of juvenile spotted seatrout and the Central had the highest abundance of juvenile red drum. Juvenile spotted seatrout hatch dates were most frequent in June, while juvenile red drum were most frequent during August. Red drum were mostly associated with detritus (52%) compared to sand (20%) or SAV (28%), whereas spotted seatrout were primarily associated with SAV (57%). Furthermore, instantaneous growth of spotted seatrout and red drum did not differ among habitats. Results of this study show how a euryhaline environment and habitat type could potentially influence fish distribution patterns. Results herein will support the development and updating of a fishery management plan for spotted seatrout and red drum in North Carolina.
Keywords: Biology; Habitats; North Carolina; Pamlico River (N.C.); Spotted seatrout--Habitat--North Carolina--Pamlico River; Red drum--Habitat--North Carolina--Pamlico River; Fishes--Dispersal--North Carolina--Pamlico River; Aquatic habitats--North Carolina--Pamlico River